ANALYSIS OF FARMING INCOME OF SWEET POTATO (Ipomea batatas L.) IN VILLAGE OF PANTI, SUB-DISTRICT PANTI, DISTRICT OF JEMBER - El Yasin, M Sandi wahyu; pudjiastutik, endang wahyu (AGRIBEST, 2019)
Meeting the food needs of the majority of Indonesia's population is still very dependent on rice. This raises problems for the Indonesian people because the amount of national rice availability is unable to cover the food needs of the population which is increasing, so that alternative substitute commodities such as Sweet Potatoes are needed. Sweet potato farmers in Village  of Panti, Sub-District of Panti, District of Jember have productivity that is difficult to increase with low prices. The purpose of this study is 1) To find out the level of income of sweet potato farming, and 2) To determine the level of efficiency of the use of farming costs. The results showed that the average total cost of sweet potato farming per hectare was IDR 22,052,029.49 with an average total farm income of IDR  63,444,198.78, so that the farm income reached IDR  41,392,169.29. Furthermore, the activity of sweet potato farming in the study location was efficient, which was marked by an R / C value of 2.15.